2015
DOI: 10.5762/kais.2015.16.9.6027
|View full text |Cite
|
Sign up to set email alerts
|

The effect of parental social support on the transition to college life and career identity of nursing undergraduate college students

Abstract: The purpose of this study was to examine influential factors for the transition to college life and career identity of nursing students and what changes social support from parents brought about to them by academic year. The subjects in this study were 542 selected students who majored in nursing in four-year universities located in Seoul and the provinces. A self-administered survey was conducted to find out their general characteristics, social support from fathers and mothers, college adjustment and career … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
4
4
0
Order By: Relevance
“…In the current study, third-and fourth-year nursing students had signi cantly better college adjustment than did second-year students (Table 2). This is consistent with previous research showing that college adjustment increases with grade level [17]. This suggests that as nursing students progress from lower to higher grades, the anxiety, stress, and burden they experienced as freshmen decrease [10], resulting in better college adjustment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, third-and fourth-year nursing students had signi cantly better college adjustment than did second-year students (Table 2). This is consistent with previous research showing that college adjustment increases with grade level [17]. This suggests that as nursing students progress from lower to higher grades, the anxiety, stress, and burden they experienced as freshmen decrease [10], resulting in better college adjustment.…”
Section: Discussionsupporting
confidence: 91%
“…Parental support helps college students trust themselves and take responsibility for their actions, which is consistent with previous research showing that parental support and affection enhance ego identity [17,27]. Affectionate parental child-rearing attitudes have a positive impact on college adjustment and help college students become more accepting, respectful, and con dent in themselves [17]. They also help increase the psychological well-being of college students and improve their interpersonal problem-solving skills [28].…”
Section: Discussionsupporting
confidence: 85%
“…This study found that the external support system of these individuals, especially parental emotional warmth in the closest relationship, enhanced nursing students' ego identity and improved their adjustment to college. Parental support helps college students trust themselves and take responsibility for their actions, which is consistent with previous research showing that parental support and affection enhance ego identity[ 18 , 33 ]. For example, universities should engage mothers and provide programs, such as education, counseling, and faculty–parent–student meetings that could improve parenting attitudes.…”
Section: Discussionsupporting
confidence: 89%
“…After examining the association between nursing students’ perceived parental child-rearing attitude and college adjustment, we revealed that paternal and maternal emotional warmth were significantly and positively correlated with college adjustment. Affectionate parental child-rearing attitudes positively affect college adjustment and help college students become more accepting, respectful, and confident in themselves [ 18 ]. Further, they help increase the psychological well-being of college students and improve their interpersonal problem-solving skills [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation